(untitled) (The Conference Hub, 2026)
The development of creative abilities is a crucial aspect of professional teacher training. Creative competencies enable teachers to design innovative learning activities, adapt to diverse educational challenges, and foster critical thinking in students. This article explores the pedagogical and psychological content of developing teachers’ creative abilities. It examines the cognitive, motivational, emotional, and activity-based components of creativity, identifies key pedagogical and psychological factors influencing its formation, and analyzes effective methods and conditions for promoting creativity in higher education. The study highlights the integrative approach necessary for the systematic development of teachers’ creative potential.